Consumers gain equivalent levels of happiness from sharing about an experience and an object - Bastos, Wilson (2021)
Purpose: This paper aims to examine how conversing about experiences and objects affects consumer happiness. In contrast to previous research focusing on conversation frequency, this paper explores how each conversation instance influences happiness. Design/methodology/approach: Four experiments use three different methodologies, namely, actual talking behavior (Study 1), recalled and mental framing interventions and measurement of the focal variables (Studies 2 and 3) and manipulation of purchase conversationality (Study 4). Findings: Consumers derive equivalent levels of happiness from each material or experiential conversation they have. When the object is highly conversational (when it generates as much conversation as experiences do), it advances as much happiness as experiences. Research limitations/implications: The findings inform precisely how the purchase conversationality model unfolds; clarify previous claims made in the literature; establish the direction of causal effect; and reveal a novel boundary condition of happiness superiority of experiences. Practical implications: The findings inform marketing managers how to optimally allocate their world-of-mouth (WOM) resources to advance consumer happiness. Additionally, this work shows a mental framing strategy able to increase WOM for objects – i.e. a tool for the manager. Originality/value: This is the first investigation to disentangle the frequency of conversation from each conversation’s ability to advance happiness. It is also the first to engage participants in an actual conversation and measure changes in their happiness, and therefore, conclusively establish the direction of the effect. Additionally, by manipulating purchase conversationality, this work demonstrates a new boundary condition associated with conversationality.